At Westonci.ca, we connect you with the answers you need, thanks to our active and informed community. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
Answer:
d1 = -1.5
dn = dn-1 *-4
Step-by-step explanation:
-1.5, 6, -24,96
The first terms is d1
d1 = -1.5
To find the common ratio divide the second term by the first term
6/-1.5 = -4
Check 6*-4 = -24
-24*-4 = 96
dn =dn-1 * -4
Answer:
D (1) = -1.5
D (n)= dn-1 *-4
Step-by-step explanation:
I know ;) hope this helps.
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.